The effect of methanol Extracts of Bitter Melon (Momordica charantia) as larvaside To Histopathology Changes Of Aedes aegypty Midgut - Ainun Masfufah (NHM PRESS, 1970)
Aedes aegypti acts a vector of dengue fever disease. Chemical pesticide application caused A. aegypti resistancy. Bitter melon (Momordica charantia) extract is valuable as an alternative pesticide replacing synthetic pesticide. The aims of this research are to find out the existence of larvicidal properties of fruit extract of Momordica charantia on Aedes aegypti larvae and to define the histopathological midgut changes of Aedes aegypti larvae. This research is an experimental research laboratory using post-test only control group design. Bitter melon fruit extract was tested in a concentration of 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 0 ppm (negative control), and temephos 1 ppm (positive control). The results showed that the LC50 value was 1833,295 ppm and LC90 value was 2467,264 ppm. Results of ANOVA showed the effect of bitter melon fruit extract concentrations against mortality of Aedes aegypti larvae with p = 0.000 (p<0.05). Midgut histopathological observations showed damage to the membrane of peritrophic, epithelial cells, and the basement membrane of midgut at different levels of concentration of bitter melon fruit extract, whereas the positive control midgut condition was normal as in the negative control (0 ppm). It was concluded that the extract of bitter melon fruit was effective as larvicide and affect to histopathological midgut of Aedes aegypti larvae.